Penatalaksanaan Intensif Badai Thyroid pada Wanita Hamil - Jufan, Akhmad Yun; Apsari, Ratih Kumala Fajar; Apriyanto (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Anesthesia management was conducted in a case of female 33 years old with G4P2A1, 35 weeks of pregnancy, type I respiratory failure, suggestive Thyroid Storm, CAP, anemia, and hypoalbuminemia. In emergency admission, patient was found dyspneic, agitated, measured BP is 117/60 mmHg, HR 153 x/min, RR 35 x/min, temperature 37,8oC, no wheezing or rales in physical examination. From ECG evaluation was STC 148 x/min, AF RVR. According to Burch and Wartofsky scoring, obtained score is 60, from temperature (score 5), tachycardia ≥140 (score 25), AF (score 10), agitated (score 10), and pregnancy as a precipitating factor (score10). Thyroid crisis can be diagnosed if scoring more than 45 points. The patient was intubated, and connected to mechanical ventilation, and admitted to HCU. In HCU, the patient was given supportive therapy, invasive monitoring such as CVC and parenteral nutrition. Causative therapy such as antibiotic administration, lugol, PTU, corticosteroid and propanolol were also given. During HCU admission, patient’s condition had not improved because of gravis anemia, after 3 days in HCU, patient was moved to ICU admission for 5 days, in 4th day of ICU admission, pregnancy was terminated, and in 5th day, patient was moved to maternal ward.